Propagation and Dispersion of Lightning-Generated Whistlers Measured From the Van Allen Probes - Ripoll, J.-F.; Farges, T.; Malaspina, D. M.; Cunningham, G. S.; Hospodarsky, G. B.; Kletzing, C. A.; Wygant, J. R. (Frontiers in Physics, 2021)
We study the propagation and attenuation of lightning-generated whistler (LGW) waves in near-Earth space (L<3) through the statistical study of three specific quantities extracted from data recorded by NASA’s Van Allen Probes mission, from 2012 to 2019: the LGW electric and magnetic power attenuation with respect to distance, the LGW wave normal angle in space, and the frequency-integrated LGW refractive index. We find that LGW electric field wave power decays with distance mostly quadratically in space, with a power varying between -1 and -2, while the magnetic field wave power decays mostly linearly in space, with a power varying between 0 and -1. Complexity of the dependence of the various quantities is maximal at the lowest L-shells (L<1.5) and around noon, for which LGW are the rarest in the measurements. In-space near-equatorial LGW wave normal angle statistics are shown for the first time with respect to magnetic local time (MLT), L-shell (L), geographic longitude, and season. A distribution of predominantly electrostatic waves is peaked at large wave normal angle. As the LGW electric power increases, the LGW wave normal angle increases. As the LGW magnetic power increases, the LGW wave normal angle distribution becomes peaked at small wave normal angle with a secondary peak at large wave normal angle. The LGW mean wave-normal angle is 41.6° with a 24° standard deviation. There is a strong MLT-dependence, with the wave normal angle smaller for daytime (34.4° on average at day and 46.7° at night). The statistics of the LGW refractive index show a mean LGW refractive index is 32 with a standard deviation of 26. There is a larger refractive index for daytime (36) than for nighttime (28). Smaller refractive index is found during Northern hemisphere summer for L-shells above 1.8, which is consistent with the so-called winter/seasonal anomaly. Cross-correlation of these wave parameters in fixed (MLT, L) bins shows that the wave normal angle and refractive index are anti-correlated. High power attenuation during LGW propagation from the lightning source to the spacecraft is correlated with large refractive index and anti-correlated with small wave normal angle.